Nutritional Quality Of Germinated Cowpea Flour And Its Application In Home Prepared Instant Weaning Food - Pongjanta, Jirapa (1998)

(untitled)
The in vitro protein quality, starch digestibility and vitamin A content of weaning food raw materials consist of rice, controlled-cowpea flour (CCF), 24h germinated- cowpea flour (24h GCF), 48h germinated-cowpea flour (48h GCF), skim milk powder and banana-pumpkin, were studied. CCF or GCF was formed to be protein rich food and banana-pumpkin was used to supplement vitamin A in the weaning food. Cowpea seeds were germinated (24h, and 48h at 25°C), dried (60- 75°C for 12 hours) and ground to form a powder. The physiochemical properties, amino acid profile, and protein quality comprise of protein digestibility corrected amino acid scores (PDCAAS), chemical score, amino acid score (AAS), essential amino index (EAAl), calculated biological value (C-BV) and FAO Score (FAOS) of treated cowpea flour were analysed. In vitro method with commercial digestive enzymes was used in assessing the protein and starch digestibility of CCF, 24h GCF and 48h GCF.